2007
DOI: 10.1177/0163278707311870
|View full text |Cite
|
Sign up to set email alerts
|

When Is Knowledge Ripe for Primary Care?

Abstract: The objectives of this study were to explore the meaning of scientific evidence as it is understood by primary care physicians. Individual interviews were conducted with actors chosen for their roles in the production and use of knowledge: 22 family physicians, 13 specialist physicians, and 6 researchers. Two situations served as points of reference for these discussions: screening for genetic breast cancer and treatment of hypertension. The results suggest that there may be a misunderstanding between the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Results of the KMM indicated that regulatory organizations focus their KT activities in the products category (see Table 1). Regulatory While these numbers were comparable to what was found in educational organizations (Cooper, 2012), the literature shows that one of the primary ways in which clinicians obtain knowledge is through colleagues (Beaulieu et al, 2008), and enhancements in networking opportunities and structure to support exchange could allow for an enhanced level of KT and evidence-based practice.…”
Section: Regulatory Organizationsmentioning
confidence: 51%
“…Results of the KMM indicated that regulatory organizations focus their KT activities in the products category (see Table 1). Regulatory While these numbers were comparable to what was found in educational organizations (Cooper, 2012), the literature shows that one of the primary ways in which clinicians obtain knowledge is through colleagues (Beaulieu et al, 2008), and enhancements in networking opportunities and structure to support exchange could allow for an enhanced level of KT and evidence-based practice.…”
Section: Regulatory Organizationsmentioning
confidence: 51%
“…This systematic review will help bridge two knowledge gaps: on the one hand, the majority of intervention studies address simple care needs rather than complex ones; on the other hand, current systematic reviews typically focus on one condition and one homogeneous population. 80–84 The studies’ heterogeneity challenge will be addressed by using an innovative mixed methods design three-step synthesis to build a taxonomy presenting various key decisional needs’ configurations.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
“…Traditional methods, however, such as journal articles and conference presentations are typically not highly effective in disseminating clinical research to healthcare providers, including physicians. 77 To increase uptake of the findings from this study, a brief video and podcast will be created that is similar to the Cochrane Library podcasts ( http://www.cochrane.org/podcasts/ ). These will summarise the key findings of these meta-analyses and their implications for practice.…”
Section: Ethics and Disseminationmentioning
confidence: 99%